Oral rehabilitation with mediate implants in a geriatric patient: Two-year follow-up (Research, Society and Development, 2021)
The objectives of this study were to evaluate implant survival and success rates in elderly patient and investigate the functional and nutritional conditions of the patient after rehabilitation treatment with a protocol-type prosthesis using mediate loading. Anterior extraction of teeth #33 to #44 was performed and after six months five Cone-Morse implants of 3.5 x 11 mm were placed. The prosthesis installation was completed after a 6-month osseointegration period and followed up for two years. There were no loss of implants, clinical signs of inflammation or presence of bone loss around the implants, and the prosthetic components were perfectly adapted. Thus, the mediate loading protocol in very elderly patients provides advantages in terms of dental prosthetic rehabilitation, as these patients require a more careful attention.